Fe3+ - Ion Selective Electrode Developed as a Detector in Flow Injection Analysis - Demir, Ersin; Kemer, Barıs; Isildak, Ibrahim; Y. Aboul-Enein, Hassan (Current Analytical Chemistry, 2015)
A new polyvinyl chloride (PVC) membrane Fe3+ ion selective electrode was constructed as a detector for the analysis Fe3+ using a home-made low-volume flow through cell. Optimum working conditions for the flow injection analysis (FIA) measurements were examined. In addition, under optimum conditions, potentiometric performance characteristics of the Fe3+ ion-selective electrode were investigated. Electrode had a linear response in the concentration range of 1.0 x 10-3-1.0 x 10-6 M (R2=0.9961, y=24.7+772.0). Reproducibility of the electrode responses was very satisfied. The potential of Fe3+ ion selective electrode was decreased intra and inter day 0.9 % and 3.7% respectively. The designed flowthrough cell system as Fe3+ detector revealed sampling rates of approximately 50 injections per hour. The obtained results in FIA were in a good agreement with AAs results at %95 confidence level for each syrups.
Keywords: determination